2007
DOI: 10.1111/j.1600-0714.2007.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MMP‐7 and MT1‐MMP in oral squamous cell carcinoma as predictive indicator for tumor invasion and prognosis

Abstract: MMP-7 was observed only in cancer cells, and MT1-MMP in both tumoral tissue and stroma. MMP-7 expression was significantly correlated with lymph node metastasis (P = 0.03; RR = 3.2). MT1-MMP showed a significant association with TIMP-2 (in N+ cases) and p53 expression (P = 0.01). MMP-7 and MT1-MMP displayed a survival relevance, and in multivariate analysis they were independent prognostic indicators, particularly in neck node-positive cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 38 publications
4
55
0
Order By: Relevance
“…However, clinicopathological variables and tumour-specific molecular markers that can identify patients with the highest risk of local recurrence have yet to be defined. 16,[18][19][20][21][22][23][42][43][44][45][46][47][48][49] Vimentin, a mesenchymal cell marker, associates with components of the cytoskeleton and membrane adhesions. Studies of human epithelial carcinomas, such as breast cancer, hepatocellular carcinoma, colon carcinoma, and prostatic adenocarcinoma, have shown that vimentin expression can be correlated with tumour invasion and a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinicopathological variables and tumour-specific molecular markers that can identify patients with the highest risk of local recurrence have yet to be defined. 16,[18][19][20][21][22][23][42][43][44][45][46][47][48][49] Vimentin, a mesenchymal cell marker, associates with components of the cytoskeleton and membrane adhesions. Studies of human epithelial carcinomas, such as breast cancer, hepatocellular carcinoma, colon carcinoma, and prostatic adenocarcinoma, have shown that vimentin expression can be correlated with tumour invasion and a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is in contrast to the Western literature, in which the tongue and mouth floor are the main sites. 22,25 In Taiwan, only 5-7% of oral cancer are graded as poorly differentiated type. 24,25 In our unpublished observation (H-C Chuang, unpublished observation), 1 of 118 documented patients (o1%) with buccal squamous cell carcinoma in our hospital is graded as poorly differentiated type.…”
Section: Discussionmentioning
confidence: 99%
“…18 However, the contribution of active MMP-7 vs MMP-7 in the progression of oral cancer has not been determined. [19][20][21][22][23] In the present study, we used tissue microarray together with immunohistochemistry and western blotting to analyze the expression of active MMP-7 in buccal squamous cell carcinoma and in normal tissues from the same patients and correlated these findings with clinicopathological features of buccal squamous cell carcinoma.…”
mentioning
confidence: 99%
“…4,13,14,20,21 For treatment of cancers, the development of highly selective and specific MT1-MMP-inhibitors has been an important but rather demanding goal. The use of a limited spectrum inhibitor against the activities of gelatinases and MT1-MMP in the treatment of lung carcinoma has been shown to be promising.…”
Section: Discussionmentioning
confidence: 99%